2017
DOI: 10.5009/gnl16079
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic Resonance Elastography and Diffusion Weighted Imaging in the Evaluation of Hepatic Fibrosis in Chronic Hepatitis B

Abstract: Background/AimsComparison of the accuracy of magnetic resonance elastography (MRE) and diffusion weighted imaging (DWI) for the diagnosis of liver fibrosis in patients with chronic hepatitis B (CHB).MethodsIn this retrospective analysis, we investigated 63 patients with CHB and liver fibrosis. DWI was performed with both breath-hold (DWI-BH) and free-breathing (DWI-FB) sequences (b=0, 500). The mean liver stiffness and apparent diffusion coefficient (ADC) were calculated by drawing regions of interest maps. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Therefore, radiomic analysis of different MRI sequences may differently perform. In this study, the textural parameters of HPs provided intermediate or high correlation with mean stiffness values (because of differences in stiffness), which have been widely proven by MRE reports to show high diagnostic performance for the classification of fibrosis [31,32]. Compared with the previously cited study reports, our study demonstrated the best diagnostic performance, and these textural features can be considered to be optimal parameters superior to conventional stiffness values.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, radiomic analysis of different MRI sequences may differently perform. In this study, the textural parameters of HPs provided intermediate or high correlation with mean stiffness values (because of differences in stiffness), which have been widely proven by MRE reports to show high diagnostic performance for the classification of fibrosis [31,32]. Compared with the previously cited study reports, our study demonstrated the best diagnostic performance, and these textural features can be considered to be optimal parameters superior to conventional stiffness values.…”
Section: Discussionsupporting
confidence: 49%
“…These results may be credited to the ability of DDC in capturing a continuous distribution of diffusion coefficients from every diffusion compartment (decided by the “no tissue compartmentalization” assumption)[ 54 , 55 ]. Beside different diffusion techniques, magnetic resonance elastography (MRE) has also been utilized in many studies for LF staging[ 8 , 25 , 56 ]. Although MRE demonstrated excellent diagnostic ability, even greater than DWI or IVIM, it is currently not widely available around the world since it requires special equipment as well as technical expertise for data acquisition and image postprocessing.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, several new methods including magnetic resonance elastography (MRE), perfusion, and gadoxetic acid-enhanced MRI, are increasingly being used to assess liver fibrosis, especially in predicting the severity of liver fibrosis [7][8][9][10]26]. MRE was more accurate than DWI for the detection and stratification of liver fibrosis in chronic hepatitis B (CHB) patients [27], however, MRE had several confounders such as concomitant liver steatosis, iron deposition, also MRE requires the use of expensive equipment and additional hardware [28,29]. Challenges for perfusion MRI of the liver including breathing motion, lack of standardized measurement, and some significant postprocessing is required for quantitative parameter analysis [26].…”
Section: Discussionmentioning
confidence: 99%